Catholic Education: A Journal of Inquiry & Practice: A Ten-Year Retrospective Review of Catholic Educational Research - Frabutt, James M.; Nuzzi, Ronald J.; Hunt, Thomas C.; Solic, Margaret A. (Catholic Education: A Journal of Inquiry and Practice, 2008)
The journal has a brief but important history, encompassing the support of major Catholic colleges and universities across the United States. In particular, the University of Dayton and the University of Notre Dame have provided a home for the editorial offices and the contributed services of the editors. As the journal prepares for a transition to its third home at Boston College, this article offers a summative and evaluative overview of the contents of the journal since its inception. Recommendations are offered regarding ways to continue to grow the field of educational research situated in Catholic schools.